Essential role of the IRF8-KLF4 transcription factor cascade in murine monocyte differentiation - Kurotaki, Daisuke (American Society of Hematology, 2013)
Monocytes regulate host defenses, inflammation, and tissue homeostasis. The transcription factor interferon regulatory factor-8 (IRF8) stimulates monocyte/macrophage differentiation, yet genome-wide understanding of the differentiation program initiated by IRF8 is lacking. By combining chromatin immunoprecipitation sequencing with gene expression profiling, we show that during IRF8-dependent monocyte differentiation, IRF8 binding occurs at both promoter-proximal and promotor-distal regions together with the transcription factor PU.1 and is associated with gene induction. Many of the promoter-distal IRF8 binding sites show an increase in histone H3 lysine 4 monomethylation, a signature for enhancers. However, about half the IRF8-induced genes were not bound by IRF8, suggesting the involvement of downstream transcription factors. Analysis of DNA motifs in cis-regulatory elements of these indirect IRF8 target genes predicted that Krüppel-like factor-4 (KLF4)—essential for Ly6C(+) monocyte development—is one such factor. Indeed, monocyte development in Irf8(−/−) mice is as defective as that in Klf4(−/−) chimeric mice. Moreover, Irf8(−/−) monocyte-dendritic cell progenitors do not express Klf4 messenger RNA. Introduction of KLF4 into an Irf8(−/−) myeloid progenitor cell line induced a subset of IRF8 target genes and caused partial monocyte differentiation. Taken together, our present results uncover genome-wide behavior of IRF8 and identify an IRF8-KLF4 axis that operates during monocyte differentiation.